Correlation of C-reactive protein levels, gene polymorphism and platelets count in Dengue infection - Sana Shamshad; Sara Khan; Ghazala Kaukab Raja; Muhammad Sheeraz Ahmad; Muhammad Javaid Asad; Tayyaba Zainab (Journal of the Pakistan Medical Association, 2020)
Objective: To determine the correlation of polymorphism in C-reactive protein gene with variation in serum levels in dengue patients. Methods: The cross-sectional study was conducted at Pir Mehr Ali Shah Arid Agriculture University, Rawalpindi, Pakistan, from October 2017 to October 2018, and comprised blood samples from dengue patients which were used to measure the serum levels of C-reactive protein. Deoxyribonucleic acid extraction followed by tetra amplification-refractory mutation system polymerase chain reaction was done to analyse the genotype variation T>G for single nucleotide polymorphism rs199953854 using allele-specific primers. Correlation of serum C-reactive protein levels with the C-reactive protein polymorphism in dengue patients was explored. Data was analysed using SPSS 21. Results: Of the 200 patients, 108(54%) had very high C-reactive protein levels, 48(24%) had levels slightly higher than the upper limit, 14(7%) had low and 30(15%) had normal levels. Also, 162(81%) patients had low platelets count. Amplification of only T alleles was noted. Conclusion: C-reactive protein levels were found to be increased with suppressed platelets count in dengue patients. Single nucleotide polymorphism rs199953854 appeared to have no polymorphism. Key Words: C-reactive protein, Dengue infection, rs199953854, Continuous...